Modeling the Kinetics of Monolith Formation by RAFT Copolymerization of Styrene and Divinylbenzene. Issue 10 (26th June 2014) - López‐Domínguez, Porfirio; Hernández‐Ortiz, Julio César; Barlow, Kristine J.; Vivaldo‐Lima, Eduardo; Moad, Graeme
Abstract The synthesis of monoliths by reversible addition‐fragmentation chain transfer (RAFT) copolymerization of styrene and divinylbenzene (DVB) at high‐crosslinker content is studied using the recently reported multifunctional polymer molecule approach. The agreement between model predictions, incorporating diffusion‐control, and experimental data from CSIRO is good for all cases analyzed. This includes examples with high‐crosslinker concentrations, which cause deviation from some of the simplifying assumptions imposed in the model.<inline-graphic xlink:href="ark:/27927/pgh1h272k91" content-type="mren201400013-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />